Health insurance integration and fertility intentions among migrant populations in China: evidence from urban–rural medical reform - Haowen Jia (BMC Health Services Research)
Abstract Background China’s integration of urban and rural medical insurance (IURMI) aims to promote equitable healthcare access for migrant populations. While social insurance is often expected to ease economic constraints and support childbearing, little is known about how IURMI influences fertility intentions among migrant women. This study examines whether expanded health coverage through IURMI affects reproductive decision-making and explores underlying mechanisms. Methods This study uses data from the 2018 China Migrants Dynamic Survey (CMDS), focusing on 53,837 migrant women aged 17 to 49. To ensure robust causal inference, it applies propensity score matching (PSM), double/debiased machine learning (DML), and instrumental variable (IV) estimation. The models control for a wide range of individual, household, and regional characteristics and include subgroup analyses to assess heterogeneity in policy effects. Results The findings show a significant negative association between IURMI and fertility intentions. The effect is stronger among women who are employed and intend to stay in cities. Rather than discouraging childbirth directly, IURMI appears to support more deliberate and long-term life planning, leading some women to postpone or reduce childbearing as they prioritize career and settlement goals. Conclusions The results highlight how institutional support through health insurance can influence fertility decisions by enhancing individuals’ ability to plan for the future. Lower fertility intentions among migrant women may reflect greater control over life trajectories rather than diminished desire for children. These findings emphasize the importance of aligning health policy with the evolving needs and preferences of urban migrant populations.